How Costly Are Labor Gender Gaps? Estimates by Age Group for the Balkans and Turkey - Cuberes, David; Muñoz Boudet, Ana Maria; Teignier, Marc (Taylor and Francis, 2019)
In this article we use survey data from the Balkan countries and Turkey to document the presence of gender gaps in the labor market and examine its economic consequences in terms of aggregate income per capita. We first show that the age of women in the labor force, as well as in the categories of employers and self-employed, are clearly below the corresponding figures for men. These gender inequalities display a slightly negative time trend and are present in all age groups, with the middle-age group displaying the lowest inequality in terms of labor force participation but the largest inequality in terms of employers share. Using a theoretical framework we calculate that, on average, the loss associated with these gaps is about 20% of income per capita. Taking into account that the weight of each age group in the total population is different, we find that the aggregate costs associated with each age group are quite similar on average.